Direct Costs Associated with Relapsed Diffuse Large B-Cell Lymphoma Therapies - Anna G. Purdum; Ryan Tieu; Sheila R. Reddy; Michael S. Broder (2019)
Abstract Background About one third of patients with diffuse large B-cell lymphoma (DLBCL) relapse after receiving first-line (1L) treatment of rituximab, cyclophosphamide, doxorubicin, vincristine, and prednisone (R-CHOP). Relapsed patients may then be eligible for second-line (2L) therapy. The study's objective was to examine health care use and costs among treated patients with DLBCL receiving 2L therapy versus those without relapse. Materials and Methods We analyzed Truven Health MarketScan® claims data between 2006 and 2015. Patients (≥18 years of age) had ≥1 DLBCL claim from 1 year before to 90 days after beginning 1L therapy, and comprised those without 2L treatment for ≥2 years (cured controls) versus those who initiated non-R-CHOP chemotherapy after discontinuing 1L therapy (2L cohort). 2L patients were further subgrouped: hematopoietic stem cell transplant (HSCT [yes/no]) and time of relapse (months between 1L and 2L): early (≤3), mid (4–12), and late (>12) relapse. The primary outcome was 1- and 2-year health care costs. Hospitalization rate and length of stay were also measured. Results A total of 1,374 patients with DLBCL received R-CHOP and fulfilled all criteria: 1,157 cured controls and 217 2L patients (87 early-relapse, 66 mid-relapse, 64 late-relapse). Twenty-eight percent of 2L patients received HSCT. Charlson Comorbidity Index/mortality risk was higher for 2L patients (4.2 [SD: 3.0]) versus controls (3.8 [2.6]; p = .039), as were yearly costs (Year 1: $210,488 [$172,851] vs. $25,044 [$32,441]; p < .001 and Year 2: $267,770 [$266,536] vs. $42,272 [$49,281]; p < .001). HSCT and chemotherapy were each significant contributors of cost among 2L patients. Conclusion DLBCL is resource intensive, particularly for 2L patients. Great need exists for newer, effective therapies for DLBCL that may save lives and reduce costs. Implications for Practice This study identified multiple important drivers of cost in the understudied population of patients with diffuse large B-cell lymphoma (DLBCL) receiving second-line (2L) treatment. Such drivers included hematopoietic stem cell transplant (HSCT) and chemotherapy. Even though HSCT is currently the only curative therapy for DLBCL, less than one third of patients receiving 2L and subsequent treatment underwent transplant, which indicates potential underuse. The variation in chemotherapy regimens suggested a lack of consensus for best practices. Further research focusing on newer and more effective treatment options for DLBCL has the potential to decrease mortality, in addition to reducing the extensive costs related to therapy options such as transplant.